2019
DOI: 10.3892/ijmm.2019.4311
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen alleviates mitochondrial dysfunction and organ damage via autophagy‑mediated NLRP3 inflammasome inactivation in sepsis

Abstract: Sepsis is a highly heterogeneous syndrome that is caused by a dysregulated host response to infection. The disproportionate inflammatory response to invasive infection is a triggering event inducing sepsis. The activation of inflammasomes in sepsis can amplify inflammatory responses. It has been reported that damaged mitochondria contribute to NACHT, LRR and PYD domains-containing protein 3 (NLRP3) inflammasome-related sepsis. Our previous study revealed that hydrogen (H 2 ) exerts anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 49 publications
0
31
0
2
Order By: Relevance
“…In the progress of sepsis, the intestinal pathogenic microorganisms and their toxins could enter the body circulation after the damage of intestinal barrier, thus causing systemic infections and MODS [38]. Studies have shown that the rst organ to be attacked is lung, and about half of sepsis patients have combined symptoms of ALI [11].…”
Section: Discussionmentioning
confidence: 99%
“…In the progress of sepsis, the intestinal pathogenic microorganisms and their toxins could enter the body circulation after the damage of intestinal barrier, thus causing systemic infections and MODS [38]. Studies have shown that the rst organ to be attacked is lung, and about half of sepsis patients have combined symptoms of ALI [11].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the biological implications of mitochondrial dysfunction in sepsis have been widely evaluated [8,21,22]. Mitochondria produce ATP by transferring electrons from substrates sequentially across four respiratory chain complexes (I to IV) and two mobile carriers (coenzyme Q and cytochrome C) to nal electron acceptors [23].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction is deemed as a key cellular event involved in the pathogenesis of multi-organ failure in sepsis, and it is secondary to tissue hypoxia and involves various toxins or mediators of in ammation that impair oxygen utilization (cytopathic hypoxia) [23,24]. There is evidence that damaged mitochondria contribute to NACHT, LRR and PYD domains-containing protein 3 (NLRP3) in ammasome-related sepsis [21]. In addition, hydrogen was found to alleviate mitochondrial dysfunction and cytokine release via autophagy-mediated NLRP3 in ammasome inactivation [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive inflammation driven by the inflammasome and IL-1β signaling pathways promotes breast cancer, fibrosarcoma, gastric cancer, and lung metastasis in a context-dependent manner [ 48 ]. Some literature has shown that H 2 can be involved in various models of inflammation based on mechanisms of mitochondrial oxidation inhibition and NLRP3 inflammasome activation ( Table 1 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Effects Of H 2 On Inflammation and Itsmentioning
confidence: 99%
“…that can permeate the cell membrane, only H 2 is able to scavenge ·OH, which is always generated inside of mitochondria [ 13 , 14 ]. It has been shown by literature that H 2 in various animal models of inflammation may be based on mechanisms to inhibit mitochondrial oxidation and NLRP3 inflammasome activation [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, the ability for H 2 to inhibit mitochondrial oxidation and NLRP3 inflammasome activation is poorly understood.…”
Section: Introductionmentioning
confidence: 99%